2002
DOI: 10.1177/089686080202200108
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Isoprene Overproduction during Peritoneal Dialysis

Abstract: Objective Isoprene is the constitutive unit of isoprenoid lipids and sterols. However, it is also a potential toxic and carcinogenic agent. Recent findings of a marked and prolonged isoprene overproduction induced by hemodialysis sessions raises the question of isoprene behavior in patients on peritoneal dialysis. Design A study with repeated measures per patient and healthy control. Setting Nephrology and Dialysis Unit and Perugia University Medical School. Patients Sixteen consecutive patients on regular con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…However, this was not the case (Figure 2). Furthermore, in contrast to findings in HD patients, no isoprene overproduction was observed during continuous ambulatory peritoneal dialysis (CAPD) by Capodicasa et al [20]. This study, together with recent evidence showing no significant differences in oxidative stress status between HD and CAPD based on circulating biomarkers [21], would argue against an oxidative genesis of increased breath isoprene.…”
Section: Discussioncontrasting
confidence: 73%
“…However, this was not the case (Figure 2). Furthermore, in contrast to findings in HD patients, no isoprene overproduction was observed during continuous ambulatory peritoneal dialysis (CAPD) by Capodicasa et al [20]. This study, together with recent evidence showing no significant differences in oxidative stress status between HD and CAPD based on circulating biomarkers [21], would argue against an oxidative genesis of increased breath isoprene.…”
Section: Discussioncontrasting
confidence: 73%
“…This characteristic breath isoprene behavior in response to dialysis has already been reported by numerous investigators [ 18 - 29 ], however, this is the first time that it is confirmed by parallel blood measurements. The advanced explanations for this phenomenon include hemodynamic stress, fluctuations of respiratory variables, or activation of metabolic pathways leading to mevalonic acid synthesis [ 19 , 21 - 23 ], nevertheless, none of them seems to be adequate [ 18 ]. Isoprene has received a growing interest in the field of breath gas analysis due to the fact that it may serve as a sensitive, non-invasive indicator of several diseases in human organism [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Monitoring of breath ethane in HD patients evidenced a rapid rise of this marker during the first minutes after initiation of dialysis, which has been attributed to treatment-induced oxidative stress [ 15 - 17 ]. Numerous investigators reported a significant increase of isoprene in breath during and after hemodialysis [ 18 - 22 ], but not during peritoneal dialysis [ 23 ]. Recently, Lee et al [ 24 ] employing breath analysis documented the exposure of dialyzed populations to some hydrocarbons and halocarbons emitted by dialyzer materials.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al reveals that mean breath isoprene levels in healthy children and adolescents increase with age, doubling every 5-6 years until reaching adult levels [31]. Capodicasa et al discovered that breath isoprene levels remain stable in CAPD patients, suggesting a minimal impact on isoprene and isoprenoidrelated lipid turnover compared to hemodialysis [32]. A very interesting study compared three approaches for assessing Kidney function in rats with induced ARF: a two-compartment model using a radiolabeled inulin tracer, estimated creatinine clearance, and breath analyte monitoring using SIFT-MS.…”
Section: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%